Prevalence of suicidal ideation and associated factors among HIV positive perinatal women on follow-up at Gondar town health institutions, Northwest Ethiopia: a cross-sectional study - Leul Belachew Zewdu; Mebratu Mitiku Reta; Niguse Yigzaw; Koku Sisay Tamirat (BMC, 2021)
Abstract Background Suicidal behaviors cover a range or continuum of acts from suicidal ideations to a series of actions, commonly known as suicidal attempts or deliberate self-harms. Though different mental disorders related studies were conducted among HIV/AIDS patients, there is a scarcity of information about the magnitude and determinants of suicidal thoughts among perinatal women. Therefore, this study aimed to determine the prevalence of suicidal ideation and associated factors among HIV positive perinatal women in the study setting. Methods An institution-based cross-sectional study was conducted among perinatal women on treatment to the prevention of mother to child transmission of HIV/AIDS at Gondar town health facilities. A total of 422 HIV-positive perinatal women were selected systematically and the data collected through medical record review and interview using a Composite International Diagnostic Interview (CIDI) toolkit. A binary and multivariable logistic regression model was employed to identify factors associated with suicidal ideation. An Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) was computed to see the strength of association between outcome and independent variables. Characteristics having less than 0.05 p-value had been taken as significant factors associated with the outcome of interest. Result The prevalence of suicidal ideation was found to be 8.2% (95% CI; 5.7 to 11.3) and with a standard error of 0.013. Perinatal depression (AOR=4.40, 95%CI: 1.63 11.85), not disclosed HIV status (AOR=3.73, 95%CI: 1.44 9.65), and unplanned pregnancy (AOR=2.75, 95%CI: 1.21 6.21) were significant factors associated with suicidal ideation. Conclusion The magnitude of suicidal ideation among HIV positive perinatal women was found to be low. Perinatal depression, non-disclosed HIV status, and unplanned pregnancy were factors significantly associated with suicidal ideation. This finding suggests the integration of mental health services with maternal and HIV support programs.